Lack of Periplasmic Non-heme Protein SorA Increases Shewanella decolorationis Current Generation - Kong, Guannan; Song, Da; Guo, Jun; Sun, Guoping; Zhu, Chunjie; Chen, Fusheng; Yang, Yonggang; Xu, Meiying (Frontiers in Microbiology, 2020)
Bacterial extracellular electron transfer (EET) plays an important role in many natural and engineering processes. Some periplasmic non-heme redox proteins usually coexist with c-type cytochromes during EET process. However, in contrast to c-type cytochromes, little is known about the roles of these non-heme redox proteins in EET. In this study, the transcriptome of Shewanella decolorationis S12 showed that the gene encoding a periplasmic sulfite dehydrogenase molybdenum-binding subunit SorA, was significantly up-regulated during electrode respiration in microbial fuel cells (MFCs), compared with that during azo-dye reduction. The maximum current density of MFCs catalyzed by a mutant strain lacking SorA (ΔsorA) was 25% higher than that of wild strain S12 (20 vs 16 μA/cm2). Both biofilm formation and current generation of the anodic biofilms were increased by the disruption of sorA, which suggests that the existence of SorA in S. decolorationis S12 inhibits electrode respiration. In contrast, disruption of SorA had no effect on respirations with oxygen, fumarate, azo dye or ferric citrate as electron acceptors by S. decolorationis S12. This is the first report of the specific effect of a periplasmic non-heme redox protein on EET to electrode, and provide novel information for enhancing the bacterial current generation.